Impact of Plastics on Human Health and Environment - Sangrajrang, Suleeporn; Ploysawang, Pattama; Promhithatron, Parinda (Thai Journal of Toxicology, 2020)
Plastic is one of the synthetic materials that has played an important role in everyday life. Plastics are inexpensive, lightweight, strong, durable properties, therefore plastics have become the popular products in the modern world. Plastic consumption has continuously increased such as plastic bag, food containers, toys and furniture. Although, use of plastic may have many benefit compared with other materials, however, many plastic chemicals may cause health problems for people. In addition, there are a variety of additives as plasticizer, stabilizer, inhibitor and pigment that are added in the plastic processing. Thus the lack of knowledge and misunderstanding plastic usage can directly harm to human health because the chemicals substances in plastic may be leached and contaminated to foods and drinks. Moreover, a large amount of consumer plastic waste is abundant burden for disposal management, especially, non-recycling plastics that can affect to ecosystem. Though plastics have many benefits but plastics have also negative impacts. The usability of plastics should consider health and safety, particularly, infants and children. On the environment, we should use the recycling or biodegradable plastics to reduce impact of environment.